Biogenic emissions by oak trees common to Mediterranean ecosystems - Simon, V; Dutaur, L (Environmental Monitoring and Assessment, 1998)
An inventory describing the fluxes of volatile organic compounds (VOCs), isoprene and monoterpenes, and other VOCs (OVOCs) from the biosphere to the atmosphere, has been constructed within the framework of the ESCOMPTE project (fiEld experimentS to COnstrain Models of atmospheric Pollution and Transport of Emissions). The area concerned, located around Berre-Marseilles, is a Mediterranean region frequently subject to high ozone concentrations. The inventory has been developed using a fine scale land use database for the year 1999, forest composition statistics, emission potentials from individual plant species, biomass distribution, temperature and light intensity. The seasonal variations in emission potentials and biomass were also taken into account. Hourly meteorological data for 1999 were calculated from ALADIN data and these were used to predict the hourly isoprene, monoterpene and OVOC fluxes for the area on a 1 km × 1 km spatial grid. Estimates of annual biogenic isoprene, monoterpene and OVOC fluxes for the reference year 1999 were 20.6, 38.9 and 13.3 kt, respectively, Quercus pubescens, Quercus ilex, Pinus halepensis and garrigue vegetation are the dominant emitting species of the area. VOC emissions from vegetation in this region contribute approximately 94% to the NMVOC (non-methane volatile organic compounds) of natural origin and are of the same order of magnitude as NMVOC emissions from anthropogenic sources. These results complete the global ESCOMPTE database needed to make an efficient strategy for tropospheric ozone reduction policy.
Keywords: biogenic VOCS; Emission inventory; isoprene; Mediterranean ecosystems; Monoterpenes (citation)